Effectiveness of the health belief model-based husband empowerment module in enhancing postpartum contraceptive support readiness: a quasi-experimental study - Feriani, Pipit; Ernawati, Rini; Kurniasari, Lia; Widjayanti, Yhenti (Universitas Airlangga, 2025)
Introduction: This study evaluated the effectiveness of a Health Belief Model (HBM)-based Husband Empowerment Module in enhancing husbands' preparedness behaviors for postpartum contraceptive support. Methods: A quasi-experimental pre-posttest control group design was conducted at two community health centers in Samarinda, Indonesia. Sixty husbands of third-trimester pregnant women were recruited through a combination of sampling, purposive sampling, and random sampling. Purposive sampling was used to choose the treatment group, and random sampling was used to select the participants, who were assigned to the intervention (n=30) and control (n=30) groups. The intervention group received a comprehensive 12-session HBM-based module delivered through antenatal care visits, home visits, group discussions, and WhatsApp support over three months. Preparedness behavior was measured using validated questionnaires assessing awareness, facilitation ability, and appreciation. Nonparametric statistical analyses were employed. Results: Post-intervention, the treatment group demonstrated significant improvements across all preparedness dimensions: awareness median scores increased from 9.0 to 11.0 (p<0.001), facilitation ability, from 5.0 to 6.0 (p<0.001), and appreciation from 4.0 to 5.0 (p<0.001), while the control group showed no significant changes (all p>0.05). Between-group comparisons revealed substantially higher preparedness in the intervention group with large effect sizes. Notably, 83.3% of intervention participants achieved good facilitation ability compared to 0% at baseline. Conclusions: The HBM-based Husband Empowerment Module effectively enhanced husbands' preparedness for postpartum contraceptive support, suggesting that structured interventions can improve husband involvement in postpartum care and maternal health outcomes.